Techno-economic and environmental risk assessment of innovative propulsion systems for short-range civil aircraft - Colmenares Quintero, Ramon Fernando (Cranfield University, 2009)
Aircraft are thought to contribute about 3.5% (IPCC, 1999) to the total radiative forcing (a measure of change in climate) of all the human activities and this figure is forecaste to increase. Future concerns for aviation’s role in climate change are mainly due to the envisaged continued growth in this sector. Growth rates for emissions are less than those for traffic growth since fuel efficiency continues to improve over the years. Despite regular improvements in fuel efficiency, emissions will carry on increasing and several solutions need to be found. The growth of air travel as well and its effect on world economics is hampered by local opposition to aircraft noise. Besides, restrictions on night take-off and landing because of aircraft noise levels leads to a negative impact on the revenues of Europe’s airlines and often results in non-European over-night airport refuelling stops. According to ACARE (Strategic Research Agenda, 2005), the sustainable development of air transport depends on achieving a significant across-the-board reduction in environmental impact, in terms of greenhouse gases, local pollution and noise around airports. Over the past 40 years the introduction of new technology has mitigated the environmental impact of aviation growth, but at the expense of increasing operating costs. Consequently, in order to make aviation more sustainable environmentally and economically, radically innovative turbofans need to be considered and optimised at the aircraft level. Based on the above, this PhD project addresses the following research questions: • The potential of different novel propulsion systems with enhanced propulsive efficiency (using advanced, contra-rotating and geared turbofans) and thermal efficiency (using intercooled and recuperated, and constant volume combustion turbofans) to meet future environmental and economical goals. • The trade-offs to be made between noise, emissions, operating cost, fuel burn and performance using single- and multi-objective optimisation case study. In order to achieve this, a multidisciplinary design framework was developed which is made up of: aircraft and engine performance, weight, cost, noise, emissions, environment, and economics and risk models. An appropriate commercially available optimiser is coupled with this framework in order to generate a powerful aero-engine preliminary design tool. The innovative turbofans were benchmarked against the baseline turbofan at the aircraft level using the A320. The multi-objective trade case study for minimum fuel burn, NOx emissions, engine direct operating cost (DOC) and noise proves that these engines are feasible to meet future noise and emissions requirements for an acceptable cost of ownership. The key driver to lower engine DOC is a considerable fall in fuel consumption. Nevertheless, acquisition and maintenance cost rise owing to hardware complexity. Consequently, further study of these engines is recommended as their environmental performance potential is considerable.